ISLAM SEBAGAI AGAMA DAKWAH DAN DINAMIKA KEBERAGAMAN MASYARAKAT NAHDLIYIN DI TUBAN - Titah Nur Auliya; Jauharotina Alfadhilah (STAI DI AL-HIKMAH, 2026)
This study aims to examine Islam as a religion of da’wah within the dynamics of diversity among Nahdliyin communities in Tuban. Islam, as a religion of da’wah, plays a significant role in fostering harmonious social life through the values of tolerance, moderation, and inclusivity. Thus, the research employs a qualitative, descriptive approach, using data collection techniques such as observation, interviews, and documentation. The findings reveal that da’wah practices among Nahdliyin communities in Tuban are predominantly cultural and adaptive to local traditions, such as tahlilan, yasinan, and religious gatherings. The da’wah carried out by kyais and religious leaders emphasizes a humanistic and moderate approach, which effectively maintains social harmony within a diverse society. However, social dynamics such as modernization, technological advancement, and the emergence of extreme religious ideologies pose significant challenges to da’wah practices. Therefore, contextual, inclusive, and culturally grounded da’wah strategies that reflect ASWAJA values are necessary to remain relevant in contemporary society. This study concludes that Islam as a religion of da’wah contributes significantly to maintaining social harmony amid the diversity of Nahdliyin communities in Tuban.